Digital Sensations : Space, Identity, And Embodiment In Virtual Reality - Hillis, Ken (Book collections on Project MUSE., 1999)
"Virtual reality is a technological reproduction of the process of perceiving the real, yet that process is filtered through the social realities and embedded cultural assumptions about human bodies and space held by the technology's creators. Digital Sensations looks closely at how the lived world is affected by representational forms generated by communication technologies, especially digital and optical virtual technologies. Through critical histories of the technologies of vision, light, space, and embodiment, Ken Hillis traces the often contradictory intellectual and metaphysical impulses behind the Western transcendental wish to achieve an ever more perfect copy of the real. He advocates that current and proposed virtual technologies reflect a Western desire to escape the body. Because virtual technologies are new, these histories also address unintended and underconsidered consequences flowing from their rapid dissemination, such as commodification and the alienation of new forms of surveillance."--Book cover.